Prevention of Brachial Plexus Injuries at Birth - Leslie Iffy (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2015)
Medicine is a fast evolving even if inexact science. Built in ancient times upon insightful observations of Egyptian, Greek and Arabic physicians [1], its progress was spearheaded by European (mainly British, French, German and Austrian) scientists after the middle ages. If the assignment of Nobel prizes is a guideline is this regard,in the last century the leadership was taken over by the United States. Both physicians and lay persons may be inclined to assume therefore, that the achievements of medical research are utilized in America in everyday practice and that progress runs parallel in all branches of medicine. As far as obstetrics is concerned these assumptions have limited validity at best. During the last century maternal and perinatal mortality rates (recognized indices of the quality of clinical care) were markedly less favorable in the USA than in Scandinavia [2] and some other developed countries. They still lag behind many others at the time of this writing.